A Modified Two-Layer Suture Technique for Transperitoneal Laparoscopic Partial Nephrectomy: Single-Center Clinical Experience - Jin, Yang; Xiong, Hui; Xia, Qinghua; Zhang, Qi (Frontiers in Surgery, 2022)
Purposes: This study aims to evaluate the feasibility and efficacy of a modified two-layer suture method during laparoscopic partial nephrectomy (LPN), by a comparative analysis with the traditional two-layer suture. Methods: A total of 60 LPN patients were enrolled in this study, of which 30 patients received the modified two-layer suture method and the remaining 30 patients underwent the traditional two-layer suture. Then, surgical characteristics including operative time, warm ischemic time (WIT), estimated blood loss/EBL, glomerular filtration rate (GFR) were recorded. Finally, univariable and multivariable linear regression analyses were used to evaluate the correlations of tumor characteristics, suture methods, and postoperative renal function. Results: There was no significant difference between two suture groups with respect to patient and tumor characteristics, postoperative creatinine level and blood urea nitrogen (BUN) level. The modified suture group showed a significantly shorter clamping time and a less GFR level reduction than the traditional two-layer suture group (15 min versus 23 min; 42.32 ± 9.48 versus 27.07 ± 7.88; P < 0.05). Additionally, the modified two-layer suture was an independent factor that influenced the clamping time and the level of GFR reduction. Conclusion: The modified two-layer suture method is feasible and effective for LPN.